2004
DOI: 10.1111/j.1475-6773.2004.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Patients with Type 2 Diabetes Mellitus in the Netherlands and the United States: A Comparison of Two Quality Improvement Programs

Abstract: Following implementation of guidelines and organizational improvement efforts, change occurred primarily in the process outcomes, rather than in the patient outcomes. Although much effort was put into improving process and patient outcomes, both complex programs still showed only moderate effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Esquemas de incentivos a los proveedores han mostrado efectividad en entornos con indicadores claros y medibles como es el caso de la diabetes, por lo que debe explorarse su uso en lo general para mejorar la atención a padecimientos crónicos. [25][26][27] La comparación entre individuos con diagnóstico previo y el resto de la población muestra, por un lado, la mayor probabilidad de comorbilidades, y por el otro, un perfil de población con mayor riesgo, por ejemplo aquellos con antecedentes familiares. La evidencia científica sobre prevención y tratamiento intensivo para diabetes indica que las acciones en ambas vertientes son costo efectivas y tienen buenos rendimientos cuando las primeras se focalizan en personas con alto riesgo de padecer diabetes y las segundas en el control de la hipertensión, el colesterol y los niveles de glucosa entre las personas que padecen la enfermedad.…”
Section: Discussionunclassified
“…Esquemas de incentivos a los proveedores han mostrado efectividad en entornos con indicadores claros y medibles como es el caso de la diabetes, por lo que debe explorarse su uso en lo general para mejorar la atención a padecimientos crónicos. [25][26][27] La comparación entre individuos con diagnóstico previo y el resto de la población muestra, por un lado, la mayor probabilidad de comorbilidades, y por el otro, un perfil de población con mayor riesgo, por ejemplo aquellos con antecedentes familiares. La evidencia científica sobre prevención y tratamiento intensivo para diabetes indica que las acciones en ambas vertientes son costo efectivas y tienen buenos rendimientos cuando las primeras se focalizan en personas con alto riesgo de padecer diabetes y las segundas en el control de la hipertensión, el colesterol y los niveles de glucosa entre las personas que padecen la enfermedad.…”
Section: Discussionunclassified
“…Benedetti and colleagues 27 found improvements in both process 31 compared programs to improve the quality of diabetes care in the Netherlands and the United States and also found both process and outcome (hemoglobin A 1c testing) improvements in both groups. The magnitude of changes (crude rate) observed in our intervention group after participation in the QIIP program is similar to that noted in an uncontrolled before-and-after evaluation of a quality-improvement initiative (Partnerships for Health) that also used the Institute for Healthcare Improvement model (9% increase in annual hemoglobin A 1c testing and 9% increase in testing for low-density lipoprotein cholesterol).…”
Section: Discussionmentioning
confidence: 99%
“…Levels are closely linked to the risk of complications, in a way that the United Kingdom Prospective Diabetes Study (19) reported that one percentage point reduction in HbA1c level resulted in a decrease of 35% incidence of microvascular complications. The evidence suggests that adherence to guidelines and increasing the frequency of HbA1c measures improve disease outcomes (6,20,21), although Valk et al (11) cautioned that increasing the number of HbA1c measurements does not automatically result in HbA1c long-term improvement. It is also reassuring that high levels of adherence were reported for measurement of blood pressure, blood lipids and blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Technical quality is one of the most important dimensions of quality in health care. It is widely accepted that improving disease specific aspects of care (technical quality) improves health outcomes (7,10,11).Technical Quality deals with the disease specific aspects of care as reflected by care processes and care outcomes (12).Technical quality differs from condition to condition and shows how well health systems deal with the specific condition (13). Service quality includes such aspects as communication or interaction between providers and patients, autonomy, attentiveness or respect for patients (14).…”
Section: Introductionmentioning
confidence: 99%